PENGARUH PENGGUNAAN MODEL PEMBELAJARAN SQ3R TERHADAP KETERAMPILAN MEMBACA PUISI PADA SISWA KELAS VIII SMP MULIA BOGOR - Ikna Napisah; Musaljon musaljon; Sofiatin Sofiatin (Jurnal Fascho: Kajian Pendidikan dan Sosial Kemasyarakatan, 2020)
This Article is the result of a study in the application of the learning model. The purpose of this study was to determine the effect of the SQ3R learning model on poetry reading skills in class VIII students of SMP Mulia Cibungbulang Bogor. This research method is an experimental method. Based on the results of the test calculation, the value of tcount is 3.032 and ttable is 2.048 with a significant level of 0.05. So it can be stated that the hypothesis H1 is accepted and H0 is rejected. So the conclusion of this study is that there is a significant influence between the SQ3R learning model on reading poetry in class VIII students of SMP Mulia Cibungbulang Bogor.